Antioxidant properties of the fruits Opuntia apurimacensis (ayrampo) and Opuntia ficus-indica (cactus pear) - Jorge, Paola (2016)
Introduction. The cactus pear contains antioxidant compounds, but it is unknown if these exist in the ayrampo. Objective. To determine the antioxidant capacity of Opuntia apurimacensis (ayrampo) and Opuntia ficus-indica (cactus pear). Design. Analytical observational study. Location. Laboratory of Clinical Biochemistry and Nutrition, Research Center of Biochemistry and Nutrition, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological material. Fresh fruit (ff) of both Opuntia apurimacensis (ayrampo) and Opuntia ficus-indica (cactus pear). Interventions. Determination of vitamin C, polyphenols and antioxidant capacity (FRAP) were performed in both fruits aqueous extracts. Results were analyzed using the Mann-Whitney U test with 95% confidence. Main outcome measures. Concentration of vitamin C and polyphenols; antioxidant capacity (FRAP). Results. Compared to the cactus pear, ayrampo presented the highest concentration of vitamin C (49.9 and 36.1 mg ascorbic acid/100 g ff), highest concentration of total polyphenols (107.3 and 68.7 mg gallic acid equivalent/100 g ff) and highest antioxidant capacity (1.1 and 0.7 mmol of Fe-II/100 g ff). Ayrampo showed the highest correlation between antioxidant capacity and vitamin C (0.91 and 0.56), and the prickly pear the higher correlation between antioxidant capacity and total polyphenols (0.98 and 0.82). Conclusions. Ayrampo showed higher antioxidant capacity compared to cactus pear.